GLOBAL GOOGLE TRENDS ANALYSIS OF ORAL CANDIDIASIS: SYNONYMS AND CLASSIFICATIONS (2004–2020) - Bakar, Abu; Arzen, Berliana; Mochtar, Rifky (Journal of Health and Dental Sciences, 2025)
Oral candidiasis can be searched on websites using its synonyms and classifications. Google Trends, a product of Google Inc., is designed to display the level of popularity of search terms. The purpose of this study was to investigate the relationship between oral candidiasis search trends and Google Trends, based on synonyms, classifications, search times, and search locations. This research is an analytical study, utilising secondary data sourced from Google Trends from 2004 to 2020. The population consists of individuals who conducted searches on synonyms and classifications of oral candidiasis from 2004 to 2020 using the Google domain. The sample was obtained through a total sampling approach, and the data were analyzed using the Pearson correlation test. The results showed that the global interest in oral thrush keywords gained the highest popularity value of 100. The results revealed a relationship between oral candidiasis and Google Trends, based on synonyms, classifications, search times, and search location distributions. DOI : 10.54052/jhds.v5n2/p177-186